The Adsorption of Cu Species onto Pyrite Surface and Its Effect on Pyrite Flotation - Bo Yang; Xiong Tong; Zhengbin Deng; Xiangwen Lv (Journal of Chemistry)
The adsorption of Cu species onto pyrite surface and its effect on flotation were investigated by using microflotation tests, first-principle calculations, and XPS surface analysis. The results indicated that the flotation of pyrite appears to be activated with CuSO4 only at alkaline pH, while being depressed at acidic and neutral pH. The adsorption of copper ions on pyrite surface was pH-dependent, and the adsorption magnitude of copper ions at alkaline pH is higher than that at acidic and neutral pH due to a strong interaction between O atom in Cu(OH)2 and surface Fe atom except for the interaction between Cu atom and surface S atom. At acidic and neutral pH, there is only an interaction between Cu atom and surface S atom. The adsorption was relatively weak, and more copper ions in solution precipitated the collector and depressed the flotation of pyrite. XPS analysis confirmed that more copper ionic species (Cu(I) and Cu(II)) are adsorbed on the pyrite surface at alkaline pH than that at acidic and neutral pH.